Evaluation of sexual dysfunction and female sexual dysfunction indicators in women with type 2 diabetes: a systematic review and meta-analysis - Rahmanian, Elham (Diabetol Metab Syndr, 2019)
Type 2 diabetes is one of the most common chronic diseases worldwide, and one of the long-term complications of this disease is sexual dysfunction in women with type 2 diabetes, which has been studied in fewer studies. The aim of this study is to determine the overall prevalence of sexual dysfunction in women with type 2 diabetes and its indicators with systematic and meta-analysis approach. The present meta-analysis study reviewed articles published foreign journals by searching the MEDLINE, Cochrane Library, Science direct, Embase, Proquest and Persian databases, including Iranmedex, Magiran, and SID between January 2000 to December 2018. The heterogeneity of studies was studied using the I(2) index and data analysis was carried out in Comprehensive Meta-Analysis software. The Meta-analysis review of 25 studies and 3892 individuals aged 70–18 years showed that the overall prevalence of sexual dysfunction in women with type 2 diabetes was 68.6% (95% CI 61.1–75.3%). The highest and lowest prevalence of sexual dysfunction was 94.4% in Iranian women with type 2 diabetes (95% CI 91.9%–96.3%) in 2014 and 17% in Italian women with diabetes Type 2 (95% CI 6.4–36.9%) in 2015. Results of meta-regression showed that with the increase in sample size and year of study, the overall prevalence of sexual dysfunction decreased and increased, respectively and the differences were statistically significant (P < 0.05). Regarding the high prevalence of sexual dysfunction in women with type 2 diabetes, health policymakers need to take appropriate measures to address this disorder in patients with type 2 diabetes.